The effect of lipophilicity on the antibacterial activity of some 1-benzylbenzimidazole derivatives - D. J. BARNA; D. D. CVETKOVIC; S. O. PODUNAVAC-KUZMANOVIC (Journal of the Serbian Chemical Society, 2008)
In the present paper, the antibacterial activity of some 1-benzylbenzimidazole derivatives were evaluated against the Gram-negative bacteria Escherichia coli. The minimum inhibitory concentration was determined for all the compounds. Quantitative structure–activity relationship (QSAR) was employed to study the effect of the lipophilicity parameters (log P) on the inhibitory activity. Log P values for the target compounds were experimentally determined by the “shake-flask” method and calculated by using eight different software products. Multiple linear regression was used to correlate the log P values and antibacterial activity of the studied benzimidazole derivatives. The results are discussed based on statistical data. The most acceptable QSAR models for the prediction of the antibacterial activity of the investigated series of benzimidazoles were developed. High agreement between the experimental and predicted inhibitory values was obtained. The results of this study indicate that the lipophilicity parameter has a significant effect on the antibacterial activity of this class of compounds, which simplifies the design of new biologically active molecules.